The Discourse of Cultural Identity Construction of Balikpapan City (A Study on Kelubut Batik Motif) - Romiana, Romiana; Riyanto, Edi Dwi; Afdholy, Nadya (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
Batik is a form of cultural expression which can express the cultural identity in Indonesia, such as in Balikpapan city. The initiative of Balikpapan City's government to showcase the cultural identity pursued through the local batik motifs produced by the local artisans, one of them is the Kelubut batik motif. Beyond its application on batik fabrics, where it is commonly featured in traditional attire, the Kelubut motif has been embraced in various public spaces and infrastructures. Therefore, this study analyzed how Kelubut batik motifs are constructed as cultural identities of Balikpapan City through the local artisans perspectives. This study employs Foucauldian discourse analysis (FDA) theory to examine the process of discourse construction in shaping the cultural identity. This study used a qualitative method. The data collection technique was interview and observations. This study found that the discourse in constructing the cultural identity through this motif is carried out through various means, such as through the philosophical values present in the embedded motifs, use of motifs in traditional cloth, use in governmental events, use in training for batik artisans, use in school uniforms, and infrastructure decoration. The identity that is created as a product of that culture is continuously developed along with the policies carried out by the government. Therefore, the findings provide new insights into how policies can construct a cultural identity in a city.